Planejamento da paisagem à conectividade entre Unidades de Conservação: estudo de caso na Bacia Hidrográfica do Sorocaba e Médio Tietê - Oehlmeyer, Amanda Santos (Universidade Federal de São Carlos, 2025)
This study analyzed the ecological connectivity among Protected Areas (PAs) in the Sorocaba and Middle Tietê River Basin (UGRHI-10), a region marked by intense urbanization, forest fragmentation, and anthropogenic pressures. The objective was to identify ecological corridors to support landscape planning and guide compensation and forest restoration strategies. To this end, three target species from the Columbidae family were selected, representing different degrees of forest dependence (Geotrygon montana, Leptotila verreauxi, and Patagioenas picazuro), used as models for defining the landscape resistance matrix. The methodology involved an integrated analysis of land cover and land use, PA zoning, interviews with managers, construction of resistance matrices with expert consultation, and modeling of least-cost paths using Linkage Mapper software. The generated routes (i.e., ecological corridors) were spatialized and overlaid with municipal boundaries, and Kernel density analyses were applied to identify connectivity hotspots. In addition, data on the reduction and deficit of Permanent Preservation Areas (PPAs) and Legal Reserves (LRs) were incorporated, enabling the definition of priority areas for environmental compensation. The results revealed a landscape dominated by agriculture (40.17%) and pastures (24.03%), with only 20.38% of forest remnants. Sorocaba stands out as the main urban center and a hub of anthropogenic pressure, while municipalities such as Ibiúna, Piedade, and Bofete hold the largest remnants of native vegetation. The analysis indicated that potential corridors are concentrated in the southeastern and northwestern regions of the basin, connecting larger forest blocks and strategic PAs, although urban and agricultural barriers limit overall landscape permeability. The integration of connectivity routes with environmental deficits highlighted Anhembi, Bofete, Botucatu, Conchas, Itu, Porto Feliz and Tietê as priority municipalities for compensation, guiding restoration actions toward the landscape’s connectivity needs. It is concluded that landscape planning at the regional scale, based on target species and spatial analysis of the resistance matrix, is an effective tool to inform public policies and forest compensation processes. The proposed approach contributes to strengthening ecological connectivity, supporting biodiversity conservation, and promoting greater environmental resilience in the face of anthropogenic pressures and land-use changes in the basin.
Landscape planning for connectivity between protected areas: a case study in the Sorocaba and Middle Tietê River Basin
Keywords: Corredores Ecológicos; Matriz de Resistência; Avifauna; Restauração Florestal; Ecological Corridors; Resistance Matrix; Forest Restoration; CIENCIAS BIOLOGICAS::ECOLOGIA; 15. Vida Terrestre; 13. Ação contra a Mudança Global do Clima; 11. Cidades e Comunidades Sustentáveis; 6. Água Potável e Saneamento